ANALYSIS OF THE RELATIONSHIP BETWEEN TELEMEDICINE USERS AND THE QUALITY OF HEALTH SERVICES FOR JKN PATIENTS AT FKTP FLAMINGO CLINIC OF SOEWONDO AIR BASE - Chairunnisa Nasution; Ermi Girsang; Santy Deasy Siregar (RADJA PUBLIKA, 2026)
Telemedicine has become an important innovation in digital health services to improve healthcare accessibility and quality, particularly for National Health Insurance (JKN) participants in Indonesia. This study aimed to analyze the relationship between telemedicine utilization and healthcare service quality among JKN patients at the Primary Healthcare Facility (FKTP) Flamingo Clinic, Lanud Soewondo, Medan. This study used a quantitative approach with a cross-sectional design. The sample was selected using a total sampling technique, involving all JKN patients who utilized telemedicine services at FKTP Flamingo Clinic during the research period. Data were collected using structured questionnaires measuring respondent characteristics (age, gender, occupation, and frequency of telemedicine use) and telemedicine service factors, including perceived usefulness, ease of use, interface quality, interaction quality, and system reliability. Data analysis was conducted using univariate analysis and bivariate analysis with the Chi-square test. The results showed that respondent characteristics such as age (p=0.614), gender (p=0.636), occupation (p=0.190), and frequency of telemedicine use (p=0.467) were not significantly associated with healthcare service quality. However, perceived usefulness, ease of use, interface quality, interaction quality, and reliability were significantly associated with healthcare service quality (p<0.05). These findings indicate that technological usability and communication quality in telemedicine services play an important role in improving patient satisfaction and healthcare service quality.